Household Vulnerability in Drinking Water and Diarrheal Disease Among Children in Coastal Villages (Journal of Preventive and Social Medicine, 2025)
Background: Access to safe drinking water is vital for health, but coastal populations frequently encounter challenges in obtaining this essential resource. The absence of a reliable drinking water supply is a significant concern for individuals living in coastal areas. To explore the connection between household vulnerability in accessing drinking water and its correlation with diarrheal diseases among children in coastal villages, we conducted a cross-sectional study. Methods: In this study, 255 households with at least one child under 18 years of age were selected using a multistage sampling technique. Respondents, mainly mothers or caregivers, were chosen based on permanent residence. Demographic data, covering education, gender, and religion, were collected. The study used both primary and secondary data for a thorough analysis, recording information on ownership of drinking water sources, types of water used, water-fetching practices, sanitation facilities, and water purification methods. Results: A substantial portion of households (71%) lacked ownership of a drinking water source, with 65.9% relying on deep tube well water. Various water sources, including shallow tube wells and rainwater harvesting, were used by other households. During natural disasters, 49% faced a crisis in safe drinking water, but 55% addressed it by saving rainwater, and 50% sought nearby safe water sources. The prevalence of diarrhea among the 255 households was 22.7% (58 cases). Statistically significant associations were observed between household vulnerability and factors like ownership of drinking water source, per capita household monthly income, household size, type of latrine used, and maternal wash behavior. Conclusion: The study emphasizes a significant connection between household vulnerability in obtaining drinking water and the increased occurrence of diarrheal diseases among children in coastal villages. To address this issue, suggested efforts include resolving ownership challenges, improving water-fetching practices, enhancing sanitation facilities, and promoting water purification methods like fitkari or boiling water to decrease the prevalence of diarrheal diseases in vulnerable households.JOPSOM 2024; 43(1): 27-32